Energy citizenship. Tools and technologies to enable transition in districts - Danila Longo; Saveria Olga Murielle Boulanger; Martina Massari; Giulia Turci (Techne)
Responses to the current energy crisis and to action against climate change have produced a wide variety of experimentations. Positive Energy Districts (PEDs) and Energy Communities (EC) are spreading as aggregators of enabling technologies, but the knowledge and skills required to plan, implement and monitor them still need to be developed. Technology alone is not enough to facilitate knowledge sharing and the experimentation and co-creation of solutions. The paper focuses on methods and tools that allow to support the creation of “energy citizens” through considerations developed in project H2020 GRETA (Green Energy Transition Actions) and in COST Action ‘PED-EU-NET’.